2011
DOI: 10.1007/s00705-011-0968-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hantaviruses in Brazilian rodents by SYBR-Green-based real-time RT-PCR

Abstract: Current knowledge of the pathogenic hantavirus indicates that wild rodents are its primary natural reservoir. Specific primers to detect the presence of viral genomes were developed using an SYBR-Green-based real-time RT-PCR protocol. One hundred sixty-four rodents native to the Atlantic Forest biome were captured in São Paulo State, Brazil, and their tissues were tested. The presence of hantavirus RNA was detected in sixteen rodents: three specimens of Akodon montensis, three of Akodon cursor, two of Necromys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…In Brazil, there are only two studies that identified hantaviruses in non-rodents reservoirs: bats ( Diphylla ecaudata and Anoura caudifer ) and marsupials ( Micoureus paraguayanus , Monodelphis iheringi and Didelphis aurita ). Sequencing the S segment of the hantavirus from both animals revealed 95% identity with the Araraquara virus, initially described in N. lasiurus rodent [238,240]. The coexistence of these animals in the same area reinforces the possibility of interspecific transmission mentioned above.…”
Section: Hantavirus Hostssupporting
confidence: 58%
“…In Brazil, there are only two studies that identified hantaviruses in non-rodents reservoirs: bats ( Diphylla ecaudata and Anoura caudifer ) and marsupials ( Micoureus paraguayanus , Monodelphis iheringi and Didelphis aurita ). Sequencing the S segment of the hantavirus from both animals revealed 95% identity with the Araraquara virus, initially described in N. lasiurus rodent [238,240]. The coexistence of these animals in the same area reinforces the possibility of interspecific transmission mentioned above.…”
Section: Hantavirus Hostssupporting
confidence: 58%
“…The concentrations of the plasmids preparation were determined by measuring the OD at 260 nm using a Nanodrop photometer (Thermo Scientific, Waltham). The plasmid copies number per microliter were determined using the formula described elsewhere [17]. All plasmids were stored at -80°C.…”
Section: Construction Of Standard Plasmidsmentioning
confidence: 99%
“…It has significantly revolutionized the detection technique for molecular diagnosis in the field of clinical microbiology, oncology, and the estimation of the interest genes expression [13][14][15][16]. Reports on HTNV detection in captured rodents based on qPCR technology have also been investigated [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, a conventional RT-PCR was able to detect Araraquara hantavirus genomes in blood and tissue samples of humans and rodents [12]. Nevertheless, molecular techniques can evolve into faster, more sensitive methods that allow for the detection and quantitation of hantaviruses in several samples.…”
Section: Introductionmentioning
confidence: 99%